Further and Further East: Steppe Land Snail, Xerolenta obvia (Gastropoda, Geomitridae), Expands its Range in Ukraine - Gural-Sverlova, N. V.; Pisaryev , S. M.; Gural, R. I. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2022)
Based on our long-term observations, collection material and literature data, the process of expanding the range of the steppe snail of Pontic-Balkan origin Xerolenta obvia (Menke, 1828) in Ukraine from the end of the 19th century to the present day is analyzed. Known findings of this species in the Pleistocene deposits of Ukraine indicate that X. obvia could migrate to Western Ukraine through the Western Black Sea region and the Podolian Upland, bypassing the Carpathian Mountains. Some records of X. obvia in the mountainous part of the Ukrainian Carpathians and in the Transcarpathian lowland (mid-20th–early 21st century) are most likely the result of anthropochory. However, even in those areas of Western Ukraine that can be considered as part of the natural range of X. obvia, this species was apparently found much less frequently at the end of the 19th and beginning of the 20th century than now. To date, X. obvia has not only spread more in Western Ukraine, but has also been recorded in Zhytomyr and Kyiv, in the Donetsk and Zaporizhzhia regions. A similar process of gradual expansion of its range is also observed in other parts of Europe. The ecological features of the species contributing to this are discussed.